Management of constipation in preventing urinary tract infections in children: a concise review - Zaffanello, Marco; Banzato, Claudia; Piacentini, Giorgio (The European Research Journal, 2019)
Objectives: Constipation is a common problem in children. Chronic functional constipation (CFC) has been a claimed conditions that may increase the risk for urinary tract infections (UTIs). Dysfunctional voiding (DV) and lower urinary tract dysfunctions (LUTD) with chronic constipation are referred to dysfunctional elimination syndromes (DES). The aim of the present review is to look at the management of constipation in children with CFC or DES in reducing the risk of recurrent UTIs. Methods: We performed a literature search on electronic databases (Pubmed and Scopus) for relevant clinical trials investigating the results of one or more treatments for children’s constipation in the term of UTIs recurrence. Results: The search strategy identified 20 valuable clinical trials. The studies are not homogenous but showed an improvement in UTIs occurrences in children managed for bowel dysfunction. Conclusion: In conclusion, children referred to a pediatric nephrologist for UTIs should include an inquiry bowel habits and those with a positive assessment for bowel dysfunction needs the collaboration with a pediatric gastroenterologist with a multidisciplinary approach.